Bewitched, bothered and bewildered : spatial emotion in contemporary art & architecture. - Budak, Adam; Munder, Heike; Rahm, Philippe; Vidler, Anthony; Wigley, Mark; Willats, Stephen (Genève : JRP Editions, 2003)
Asdam, Knut ; Aziz + Cucher ; Bonvicini, Monica ; Büchel, Christoph ; Casebere, James ; Décosterd, Jean-Gilles ; Rahm, Philippe ; Dibbets, Jan ; Fischer, Urs ; Giger, H.R. ; Jozefowicz, Katarzyna ; Kapoor, Anish ; Libeskind, Daniel ; Matta-Clark, Gordon ; Müller, Matthias ; Noble, Paul ; Schinwald, Markus ; Sosnowska, Monika ; Thek, Paul ; Willats, Stephen ; Wilson, Jane & Louise
biog., ind. tent., gr. tent. p. 182-188
Bewitched, bothered and bewildered : spatial emotion in contemporary art & architecture (1). Exhibition. Bewitched, bothered and bewildered : spatial emotion in contemporary art & architecture (2). Laznia Centre for Contemporary Art Gdansk. Migros Museum für Gegenwartskunst Zürich. 2002-07-12. 2003-03-22. 2002-09-14. 2003-05-25
boek